Pacing and predictors of performance during cross-country skiing races: A systematic review - Thomas Stöggl; Barbara Pellegrini; Hans-Christer Holmberg (Elsevier, 2018)
Background: Cross-country skiing (XCS) racing, a popular international winter sport, is complex and challenging from physical, technical, and tactical perspectives. Despite the vast amount of research focusing on this sport, no review has yet addressed the pacing strategies of elite XCS racers or the factors that influence their performance. The aim was to review the scientific literature in an attempt to determine the effects of pacing strategy on the performance of elite XCS racers. Methods: Four electronic databases were searched using relevant subject headings and keywords. Only original research articles published in peer-reviewed journals and the English language and addressing performance, biomechanics, physiology, and anthropometry of XCS racers were reviewed. Results: All 27 included articles applied correlative designs to study the effectiveness of different pacing strategies. None of the articles involved the use of an experimental design. Furthermore, potential changes in external conditions (e.g., weather, ski properties) were not taken into consideration. A comparable number of studies focused on the skating or classical technique. In most cases, positive pacing was observed, with certain indications that higher-level athletes and those with more endurance and strength utilized a more even pacing strategy. The ability to achieve and maintain a long cycle length on all types of terrain was an important determinant of performance in all of the included studies, which was not the case for cycle rate. In general, uphill performance was closely related to overall race performance, with uphill performance being most closely correlated to the success of female skiers and performance on flat terrain being more important for male skiers. Moreover, pacing was coupled to the selection and distribution of technique during a race, with faster skiers employing more double poling and kick double poling, less diagonal stride, and more V2 (double dance) than V1 (single dance) skating across a race. Conclusion: We propose that skiers at all levels can improve their performance with more specific training in techniques (i.e., maintaining long cycles without compromising cycle rate and selecting appropriate techniques) in combination with training for endurance and more strength. Furthermore, we would advise less experienced skiers and/or those with lower levels of performance to apply a more even pacing strategy rather than a positive one (i.e., starting the race too fast). Keywords: Classic style, Competition, Cycle characteristics, Positive pacing, Skating